Pengaruh Pola Asuh Orang Tua terhadap Kepribadian Anak pada Siswa SMA: Bimbingan dan Konseling Keluarga - Budi Hendrawan; Prio Utomo; Zubaidah Zubaidah (Indonesian Journal of Guidance and Counseling Studies, 2025)
Background: Parental parenting styles play a crucial role in children's personality development, influencing various aspects such as self-esteem, independence, and social skills. Objective: The purpose of this study is to analyze the influence of parental parenting styles on children's personality development in high school students, focusing on how authoritative, authoritarian, permissive, and neglectful parenting styles affect children's character. Method: This study uses a quantitative approach with a correlational design. Data were collected through questionnaires given to parents and students, as well as interviews to obtain more in-depth information about the parenting styles applied. Data analysis was performed using regression tests to determine the influence of parenting styles on children's personality development. Result: Parental parenting styles have a significant influence on children's personality development. Authoritative parenting is associated with better self-esteem, independence, and social skills, while authoritarian and permissive parenting tends to hinder children's positive development. Conclusion: Good parenting, remarkably authoritative parenting, has a significant influence on the development of a healthy child's personality. Therefore, parents are expected to employ supportive parenting styles, enabling children to develop into independent, confident individuals with strong social skills. Contribution: This study makes a significant contribution to the literature in the field of developmental psychology and family counseling. Keywords: Family guidance and counseling; Parental parenting styles; Children's personality; Junior high school students.